2021
DOI: 10.3389/fpubh.2021.610824
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Experience of Public Health System Construction in China's COVID-19 Prevention

Abstract: Background: China's experience in the process of COVID-19 prevention provides a reference for other countries in the world. This article studied the experience of public health system construction in China's COVID-19 prevention.Methods: Based on literature review and theoretical analysis, this paper constructs a theoretical framework of national public health system construction in health crisis. Based on this theoretical framework, combined with the policies and measures formulated by the Chinese government i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…27 Possessing largest average quantity of beds, Heilongjiang holds a lower level of the accumulative Science and Technology Evaluation Metrics of Chinese hospital, 42 which has aggravated the negative impact of medical resources shortage during COVID-19 epidemic. Although there is precedent in China for the rapid and efficient establishment of mobile hospitals to increase bed capacity during an epidemic, 43 it would be strenuous for this strategy to solve the problem once a nationwide, mega-volume of excess hospitalizations are advent within a short span of time.…”
Section: Discussionmentioning
confidence: 99%
“…27 Possessing largest average quantity of beds, Heilongjiang holds a lower level of the accumulative Science and Technology Evaluation Metrics of Chinese hospital, 42 which has aggravated the negative impact of medical resources shortage during COVID-19 epidemic. Although there is precedent in China for the rapid and efficient establishment of mobile hospitals to increase bed capacity during an epidemic, 43 it would be strenuous for this strategy to solve the problem once a nationwide, mega-volume of excess hospitalizations are advent within a short span of time.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that strengthening basic public services, particularly the equitable distribution of medical resources, was conducive not only to the promotion of inclusive growth (Saniya et al 2021 ) but also to the reduction of CO 2 emissions and, therefore, the promotion of green growth (Faik et al 2021 ). Further, unhealthy interactions among IGG subsystems may lead to coronavirus transmission, and the discrepancy between medical demand and expenditure has increased as a result of the COVID-19 pandemic (Zhang 2021 ). In practice, evidence can also be found.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from the study highlighted the importance of establishing a sustainable primary medical system that meets demands. A robust primary medical system can minimize complications and fatalities caused by the COVID-19 crisis (Schmidt et al, 2022; P. F. Zhang, 2021). This system should actively monitor the dynamic pandemic situation, e ciently execute contact tracing and quarantine measures, implement follow-up and monitoring of patients to support safe home care, and facilitate the rapid referral of the most severe or deteriorating cases to hospitals.…”
Section: Discussionmentioning
confidence: 99%